Draft Annual Plan (2008-09) Proposals - Planning Commission (Planning Commission, 2008)
Manipur is one of the Border States in the northeastern part of the country having an international boundary of about 352 kms. long stretch of land with Myanmar in the east. It is bounded by Nagaland in the north, Assam in the west and Mizoram in the south. It has a total area of 22327 sq kms with a total population of 21.67 lakhs excluding the population of Mao Maram, Paomata and Purul sub-divisions of Senapati District as per 2001 census. It lies between latitude 23.8° N to 25.7° N and longitude 93.5° E to 94.8° E. 1.8 Manipur attained statehood in the year 1972. It is one of the States which was created on historical consideration and not on administrative and financial viability. It has no big industries or big projects to create employment opportunities for the increasing work force.
Government of Manipur Planning Department